If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -8) + 3(7x + 6) = 6(8x + 3) + -8x Reorder the terms: 5(-8 + 3x) + 3(7x + 6) = 6(8x + 3) + -8x (-8 * 5 + 3x * 5) + 3(7x + 6) = 6(8x + 3) + -8x (-40 + 15x) + 3(7x + 6) = 6(8x + 3) + -8x Reorder the terms: -40 + 15x + 3(6 + 7x) = 6(8x + 3) + -8x -40 + 15x + (6 * 3 + 7x * 3) = 6(8x + 3) + -8x -40 + 15x + (18 + 21x) = 6(8x + 3) + -8x Reorder the terms: -40 + 18 + 15x + 21x = 6(8x + 3) + -8x Combine like terms: -40 + 18 = -22 -22 + 15x + 21x = 6(8x + 3) + -8x Combine like terms: 15x + 21x = 36x -22 + 36x = 6(8x + 3) + -8x Reorder the terms: -22 + 36x = 6(3 + 8x) + -8x -22 + 36x = (3 * 6 + 8x * 6) + -8x -22 + 36x = (18 + 48x) + -8x Combine like terms: 48x + -8x = 40x -22 + 36x = 18 + 40x Solving -22 + 36x = 18 + 40x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40x' to each side of the equation. -22 + 36x + -40x = 18 + 40x + -40x Combine like terms: 36x + -40x = -4x -22 + -4x = 18 + 40x + -40x Combine like terms: 40x + -40x = 0 -22 + -4x = 18 + 0 -22 + -4x = 18 Add '22' to each side of the equation. -22 + 22 + -4x = 18 + 22 Combine like terms: -22 + 22 = 0 0 + -4x = 18 + 22 -4x = 18 + 22 Combine like terms: 18 + 22 = 40 -4x = 40 Divide each side by '-4'. x = -10 Simplifying x = -10
| n-3n=14-14n | | 2x-8=-3x+8 | | -3(5n-5)+2n= | | q=p(r+a) | | 4(3x+1)+1=2(x-5) | | -2+5x=-57 | | -2(-17+3X)=-6x+34 | | 2(x+4)=-2(x-4) | | 15x+12x=108 | | -9x-15y-7x+10y= | | 4a+7=2a+21 | | 7x-11=60 | | 9(x+2)-5= | | -6n=-1 | | 39-16-6q=53 | | 12x+(-9y)+(-5x)+4y= | | 34-9+7k=88 | | 5x+34=7x+32 | | x^2+10x-17=7 | | 11j+15=16j+3 | | 1.9x+4.5=10.2 | | -5X+200=0 | | 2-y=2y+8 | | 17=13-d | | 15-1(3-5y)=2(y+3) | | X^2+7=53 | | x+(x+7)+2(x+7)=53 | | x(5x^2+8x-9)=-2 | | (2x+4)*(4x-1)=0 | | 5+6X=11+7x | | 7+10x-4=7x+57-3x | | X^2-53=x |